Empowering Communities through Sustainable Tourism: A Systematic Review of Participation, Governance, and Resilience - Sumandi, Sumandi; Rizkikadduhani, Annisa (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
This study conducts a systematic literature review of academic research published between 2013 and 2023, focusing on the role of local community participation in sustainable tourism. Using the PRISMA 2020 protocol, a total of 111 peer-reviewed journal articles were identified from Scopus, Web of Science, and ScienceDirect. The synthesis reveals five key thematic areas: participation mechanisms and governance structures, economic empowerment and livelihood diversification, cultural identity and heritage, barriers to meaningful participation, and long-term sustainability through community resilience. The findings show that while community participation is widely promoted in policy and academic discourse, its actual implementation varies greatly in depth and effectiveness. Genuine participation characterized by co-management, local ownership, and inclusive governance leads to improved socio-economic outcomes and greater resilience. However, many initiatives remain tokenistic, hindered by elite dominance, lack of technical capacity, and institutional constraints. Cultural commodification also emerges as a risk when local voices are excluded from decision-making. This review contributes to the literature by offering a decade-long synthesis of how community participation is conceptualized and applied in sustainable tourism. It also highlights practical implications for policymakers, NGOs, and tourism planners. Strengthening local governance and long-term institutional support is essential to ensure that tourism development is both inclusive and sustainable.